(3efXeI GdJLGQI GdYGdejIs - (3Sgjd MSjf(B, (3GdaJdGhjs ((3YeGf(B:s (3OGQ GdKbGaI ddfSQ hGdJhRjY(B,s, 2006)
-(3GdJfXje GdbGfhfj defXeI GdJLGQI GdYGdejI ,CgOGa efXeI GdJLGQI GdYGdejI heHGOFgG ,GdJMOjGJ GdJj JhGLg efXeI GdJLGQI GdYGdejI(B.s
(3GdeQGLY U(B.345 ((3GbJfGAGJ (B2014 (3f(B1)s
Keywords: (3GdJLGQI GdNGQLjIs; (3GdefXeGJ GdOhdjIs; (3efXeI GdJLGQI GdYGdejIs